Combinación de agentes biológicos para el control de enfermedades del fruto de cacao (Theobroma Cacao L). - Peñaherrera Villafuerte, Sofía Lorena (2013)
In Ecuador, more than 80% of the cocoa orchards are cultivated by small farmers, without receiving crop management, where two fungal pathogens Moniliopthora perniciosa (witches' broom) and M. roreri (moniliasis) destroy between 40 to 60% of production. There are several management options available to reduce this impact, including cultural practices, chemical control and resistance. The Plant Protection Department INIAP has a collection of biological control agents for cacao which three strains of Trichoderma spp (T. koningiopsis, T. stromaticum and T. ovalisporum) are those used in this research. The objectives were to determine the combination of biological agents for controlling diseases of fruit of cocoa (Theobroma cacao L.), and determine the efficiency of different combinations of three species of Trichoderma and Bacillus pumilus control fruit rot by M. roreri and M. perniciosa in cocoa plantation. Furthermore establish the appropriate formulation for reducing the incidence of M. roreri in cocoa. We also compared the effect of these species at field level compared with the fungicide copper hydroxide. The experiment was conducted in the laboratory of Plant Pathology EET - Pichilingue and consisted of two stages. In the first stage, they used, the combinations of biological control agents in a plantation established in the field (local clones Lot) where it was evident the effect of biological control agents in the amount of healthy ears, Cherrelles wilt. In the second phase was recovered, isolated and purified the 3 strains of Trichoderma inoculated with Bacillus different behavior as occurred in any of the evaluations it was recovered. This confirms the Trichoderma spp as an option for handling fruit diseases in cocoa farming.